Fatty Acid Biosynthesis Pathways in Methylomicrobium buryatense 5G(B1) - Demidenko, Aleksandr; Akberdin, Ilya R.; Allemann, Marco; Allen, Eric E.; Kalyuzhnaya, Marina G. (Frontiers in Microbiology, 2017)
Methane utilization by methanotrophic bacteria is an attractive application for biotechnological conversion of natural or biogas into high-added-value products. Haloalcaliphilic methanotrophic bacteria belonging to the genus Methylomicrobium are among the most promising strains for methane-based biotechnology, providing easy and inexpensive cultivation, rapid growth, and the availability of established genetic tools. A number of methane bioconversions using the microbial cultures have been discussed, including the derivation of biodiesel, alkanes, and OMEGA-3 supplements. These compounds are derived from bacterial fatty acid pools. This study investigates fatty acid biosynthesis in Methylomicrobium buryatense 5G(B1). Most of the genes homologous to typical Type II fatty acid biosynthesis pathways could be annotated by bioinformatics analysis, with the exception of FA transport and regulatory elements. Different approaches for improving fatty acid accumulation were investigated. These studies indicate that both fatty acid degradation and acetyl- and malonyl-CoA levels are bottlenecks for higher level fatty acid production. The best strain generated in this study synthesizes 110.7 mg/gDCW of extractable fatty acids, which is approximately 20% more than in original strain. A candidate gene for FA-biosynthesis regulation, farE, was identified and studied. Its deletion results in drastic changes to the FA profile, leading to an increased pool of C18- fatty acid methyl ester. The FarE-regulon was further investigated by RNA-seq analysis of gene expression in farE-knockout mutant and farE-overexpressing strains. These gene profiles highlighted a novel set of enzymes and regulators involved in fatty acid biosynthesis. The gene expression and fatty acid profiles of the different farE-strains support the hypothesis that metabolic fluxes upstream of fatty acid biosynthesis restrict fatty acid production in the methanotroph.